Snow cover mapping, topographic controls and integration of meteorological data sets in Din-Gad Basin, Central Himalaya. (20th February 2021) - Yadav, Jairam Singh; Misra, Anshuman; Dobhal, D.P.; Yadav, R.B.S.; Upadhyay, Rajeev
Abstract: Din-Gad basin, located in central Himalaya is occupied by the Dokriani glacier in upper reaches. Landsat TM, OLI and Sentinel MSI data sets of seven years from 2009 to 2011 and 2013 to 2016 are utilized to map the areal extent of snow-cover, its seasonal variability and topographical controls (elevation, aspect, and slope). Coefficient of Variation (CV) in Snow Cover Area (SCA) below the elevation of 5000 m asl is high ( 2.0), and is low at higher elevations. CV is also higher for southern as compared to northern aspects. Meteorological data (temperature, relative humidity, and solar radiation) from Automatic Weather Stations (AWSs) is utilized to compute isotherms ( 0, 1, and 2 °C) by extrapolation method using Near-surface Temperature Lapse Rate (NSTLR). These data sets are integrated and presented by graphical as well as on Geographical Information System (GIS). Month-wise isotherms closely correspond with snow-cover extent during ablation season, suggesting that the extrapolated temperatures represent a significant proxy for depletion pattern, while month-wise and hourly isotherms deviate largely from the SCA during winter months due to snow events. Elevation zones above 5200 m asl retain snow throughout the year, indicating proximity with Equilibrium Line Altitude (ELA). The effects of Relative Humidity (RH) and solar radiation on melting history during different seasons have also emerged. The proposed methodology is efficient and reliable in terms of estimating the depletion patterns, and deriving the isotherms that can be applied to other comparable snow-covered areas. Graphical abstract: Image 1